FAULT DETECTION FOR MOTOR DRIVE CONTROL SYSTEM IN INDUSTRIAL ROBOTS USING CNN-LSTM BASED OBSERVERS - Mrs.B.Laxmi Kalpana, G.Divya , Sunkari Sailakshmi , M.Sowjanya, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The complex working conditions andnonlinear characteristics of the motor drivecontrol system of industrial robots make it difficult to detect faults. In this paper